Spatio-temporal control of post-Golgi exocytic trafficking in plants - Elliott, L; Moore, I; Kirchhelle, C (Company of Biologists, 2020)
A complex and dynamic endomembrane system is a hallmark of eukaryotic cells and underpins the evolution of specialised cell types in multicellular organisms. Endomembrane system function critically depends on the ability of the cell to (1) define compartment and pathway identity, and (2) organise compartments and pathways dynamically in space and time. Eukaryotes possess a complex molecular machinery to control these processes, including small GTPases and their regulators, SNAREs, tethering factors, motor proteins, and cytoskeletal elements. Whereas many of the core components of the eukaryotic endomembrane system are broadly conserved, there have been substantial diversifications within different lineages, possibly reflecting lineage-specific requirements of endomembrane trafficking. This Review focusses on the spatio-temporal regulation of post-Golgi exocytic transport in plants. It highlights recent advances in our understanding of the elaborate network of pathways transporting different cargoes to different domains of the cell surface, and the molecular machinery underpinning them (with a focus on Rab GTPases, their interactors and the cytoskeleton). We primarily focus on transport in the context of growth, but also highlight how these pathways are co-opted during plant immunity responses and at the plant–pathogen interface.